Can neutrophil–lymphocyte ratio be independent risk factor for predicting acute kidney injury in patients with severe sepsis?. (14th November 2014) - Yilmaz, Hakki; Cakmak, Muzaffer; Inan, Osman; Darcin, Tahir; Akcay, Ali
Abstract: Aim : Neutrophil–lymphocyte ratio (NLR) is an easily calculated, sensitive, and accurate marker for prognosis and diagnosing sepsis, cardiovascular disease and cancer. As sepsis and septic shock are main causes of acute kidney injury (AKI) intensive care unit (ICU), we investigated whether NLR is an early predictor of AKI in patients with severe sepsis. We compared NLR's predictive power with that of other inflammation-related variables. Methods : Between December 2011 and November 2013, we enrolled 118 consecutive cases with severe sepsis admitted to ICU in this retrospective study. Levels of C-reactive protein (CRP), NLR, and white blood cell count (WBC) were recorded on admission and patients' renal function was monitored for seven consecutive days. Results : The rate of AKI occurrence 7 days after enrollment was 57.6%. NLR levels were higher in the AKI group (Group 1) than in the non-AKI group (Group 2) on the day of ICU admission ( p < 0.001). AKI development was independently associated with NLR, Acute Physiology and Chronic Health Evaluation II (APACHE II) and duration of invasive mechanical ventilation (MV) in multivariate logistic regression analysis. The area under the receiver-operating characteristic (ROC) curve of NLR for predicting AKI was 0.986, which was superior to WBC and CRP ( p < 0.05). The cut-off value of 10.15 for NLR had the highest validity for predicting AKI in patients with severe sepsis. The sensitivity, specificity, negative-predictive value (NPV), and positive-predictive value (PPV), for this cut-off value was 90.2%, 92.9%, 90.4%, and 92.7%, respectively. Conclusion : NLR is superior to CRP, and WBC for predicting the development of AKI in patients with severe sepsis.